Handbook of industrial organization - Schmalensee, Richard; Willig, Robert D. (Amsterdam ; New York : North-Holland ; New York, N.Y., U.S.A. : Sole distributors for the U.S.A. and Canada, Elsevier Science Pub. Co., 1989)
This volume aims to serve as a source, reference, and teaching supplement for industrial organization (or industrial economics), the broad field within microeconomics that focuses on business behavior and its implications both for market structures and processes, and for public policies towards them.
Volume 2.
Includes bibliographical references and index.
ne 24/01/2019
Loans
Keywords: Industrial organization (Economic theory).